L’anthropocentrisme au défi de l’antispécisme - Réjane Sénac (Recherches Sociologiques et Anthropologiques)
Debates surrounding the Anthropocene and its various declensions, including the Androcene, Capitalocene, Colonialocene, Plantatiocene, and Secularocene, challenge the assumption of human superiority as a moral and political foundation. As the political community has gradually expanded to include animalized human groups, particularly women and racialized individuals, the question arises of whether the political and legal continuum should also be extended to non-human animals and other forms of life. In this perspective, Sue Donaldson and Will Kymlicka invite us to rethink categories of domination in a way that includes both individuals assigned to marginalized human groups and non-human animals, who are often positioned as sub-human.This approach begins with the recognition of the interdependence of all beings sharing the same ecological space, along with the acknowledgment of animal agency, understood as the reappropriation of a degree of autonomy in their relations with humans. The envisioned horizon is that of a positive zoopolitics rooted in emancipation. In other words, the central issue becomes the politicization of the animal question, which must no longer be addressed solely in moral terms but also by recognizing non-human animals as actors within the political and legal community.We explore this politicization by examining how antispeciesism contributes to the ongoing, though still marginal, debate on the relationship between emancipation and anthropocentrism. After outlining the challenges involved in applying the principle of equality to non-human animals, we analyze the ways in which antispeciesism confronts both the desire to preserve the existing social and political order and the dominant understanding of emancipation. This final dimension will be explored through our qualitative study of contemporary mobilizations against injustice..